Multibeam antenna design - Ibrahim, Siti Zuraidah (Penerbit UTM, 2007)
The topic of multibeam antenna constructed using Butler Matrix as a beamforming network (BFN) has received much attention due to its simplicity and low cost of implementation. It becomes more popular nowadays, as it is capable to reduce co-channel interference and then increase the channel capacity of a system. Co-channel interference could be reduced using multibeam antenna by focusing directional beams to the desired user direction, and be null to undesired user directions. In fact, there are few popular methods of constructing a multibeam antenna such as using digital beamformer, Blass Matrix and lens based beamformer, but the simplest one is by integrating linear antenna array with Butler Matrix. Butler Matrix is a well known BFN where it has a capability of producing multiple independent beams that directed at different directions. The number of generated beams, the beams angle directions, HPBW of each beams and total coverage angle of multibeam antenna could be varied dependent on the antenna array design configuration itself. The radiation patterns characteristics of the multibeam antenna could be analyzed through pattern multiplication theorem of antenna array.